Effect of modified atmosphere packaging on the shelf-life and quality of dragon fruit - Cuartel, Ned Gabrielle D.; Rumbaoa, Rowena Grace O. (Quezon City College of Home Economics, University of the Philippines Diliman, 2013)
This study explored and characterized Modified Atmosphere Packaging (MAP) systems for dragon fruits to prolong shelf life. Passive modification was achieved by natural respiration of the fruits enclosed in polypropylene (PP), low-density polyethylene (LDPE), & polyvinylchloride (PVC) film indicated by the decline in the concentration of O2 & increase in the CO2 in the bags' headspace. Significant (p<0.05) increase for both O2 and CO2 levels were observed in the headspace for nylon polyethylene(NYPE)enclosed dragon fruits.These MAP system showed significant effects (p<0.05) on the fruits Visual Quality Rating (VQR), Hunter Lab color values, and pH. Results showed that PP, LDPE, and NYPE are viable packaging treatments for MA-packed dragon fruit. PVC-treated fruits exhibited similarities with control. PP- and LDPE-packed dragon fruits achieved a shelf-life that is a week longer than the untreated fruits while NYPE-treated reached a whole month of shelf-life with still acceptable quality.
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Dragon fruit; Fruit -- Packaging -- Philippines